PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP PROSES KEPUTUSAN PEMBELIAN FOLLOWERS INSTAGRAM @agakenyang - Kurniawati, Yosita; Kaligis, Retor AW (Istek Widuri Jakarta, 2020)
The growth of the culinary industry in Indonesia is experiencing rapid growth. In addition to progress in the culinary field, the advancement of information technology has experienced rapid growth. Social media is one type of content thatis widely accessed by internet users in Indonesia, and Instagram is classified as a social media platform that has the seventh most users in the world. For that the use of social media for the delivery of an electronic message is needed in the digital era today. Some people need someone who is able to be trusted and convince themselves in the process of making purchasing decisions regarding the product or brand that will be consumed. The existence of electronic word of mouth delivered through internet media makes it the most effective, easy and rightchoice because it can prevent and reduce the uncertainty that wil occur in the purchasing decision process. The concept used in this study is electronic word of mouth and the process of purchasing decisions. The methodology used in this research is quantitative explanative. The population taken by the researcher is all followers on the @agakenyang Instagram account as many as117.000 followers as of June 16th,2019 with probability sampling techniques and response rates as sampling techniques. With a sample of 151 respondents, it was found that there was an effect of electronic word of mouth by foodie through Instagram social media on the purchasing decision making process. With the value of t count is greater than the value of t table then Ho is rejected and Ha is accepted. The correlation coefficient of 0.756 is between 0.601 – 0.8000, so it can be concluded that the strength of the relationship is strong.